Balance in Positive Emotional Expressivity Across School Contexts Relates to Kindergartners' Adjustment. Issue 1 (2nd January 2018) - Hernández, Maciel M.; Eisenberg, Nancy; Valiente, Carlos; Spinrad, Tracy L.; Berger, Rebecca H.; VanSchyndel, Sarah K.; Thompson, Marilyn S.; Southworth, Jody; Silva, Kassondra M.
ABSTRACT: Positive emotional expressivity has been associated with increased social competence and decreased maladjustment in childhood. However, a few researchers have found null or even positive associations between positive emotional expressivity and maladjustment, which suggests that there may be nuanced associations of positive expressivity, perhaps as a function of the social context in which it is expressed. We examined whether observed positive emotional expressivity balance across peer-oriented/recreational and learning contexts predicted kindergarten children's adjustment ( N = 301). Research Findings : Higher positive expressivity during lunch/recess compared to positive expressivity in the classroom was associated with lower teacher–student conflict, externalizing behaviors, and depressive symptoms. In addition, overall positive emotional expressivity predicted lower externalizing behaviors as well as lower depressive and anxiety symptoms. Practice or Policy : The results suggest the importance of assessing observed positive emotional expressivity in context as a potential indicator of children's maladjustment risk and the need for children to adapt their emotions to different contexts. Implications for assessing and supporting positive emotional expression balance and training emotional regulation in school are discussed.